Clinical Forum: canine pancreatitis and biliary duct obstruction. Issue 2 (26th May 2013) - Walker, David; Cook, Audrey; McLauchlan, Gerard; Pratschke, Kathryn; Simpson, James
<x xml:space="preserve">Abstract</x> Part 1: The medic's perspective This clinical forum will review pancreatic disease in dogs, primarily focusing on patients that go on to develop obstruction of the biliary tree. A panel of specialists will be asked a series of commonly asked questions relating to pancreatitis and concurrent biliary tract obstruction, with varying views expressed! Over the coming weeks, further articles on this topic will be published, giving both an imager's and surgeon's perspective on canine pancreatitis and biliary duct obstruction.